The washing powder wars : Ariel versus Omo - Bowen, Amanda; Saini, Yvonne ([London] : SAGE, 2016)
In November 2014, Omo - Unilever South Africa's premium washing powder brand - faced the biggest challenge yet to its 50-year dominance of the South African washing powder market. Proctor and Gamble had launched Ariel in May of the previous year, and a recent survey had shown that the brand had already gained loyalty among 10% of South African consumers. As Themba Ndlovu, Unilever's newly appointed marketing manager, prepared for an Omo marketing strategy meeting the next day, he wondered what could be done to ensure that Omo defended its market share - and grew - in the face of stiff competition.
Originally Published in: Bowen, A., & Saini, Y. (2015). The Washing Powder Wars: Ariel versus Omo. WBS-2015-1. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Unilever South Africa; Marketing -- Case studies